STRATEGI DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN IKM TS ALUMUNIUM - Lyna Amelia Khan; Indah Kurniawati (Politeknik Negeri Sriwijaya, 2022)
Technological developments have shown tremendous progress. His presence has had a huge impact on mankind in various aspects. In the current development of e-commerce, the concept of digital marketing continues to develop through online applications or platforms whose purpose is to help business people. Digital transactions are increasingly being used, leading business actors to be able to take advantage of the internet very well. The main problems faced by managers are the lack of marketing initiatives by employees and lack of understanding. One way to promote and market IKM TS Aluminum is by improving the marketing system and making more use of its digital marketing by using this digital brochure Imooji and justifying the feed on Instagram to make it look more attractive. After the justification of the Instagram feed and the creation of an online brochure, it is hoped that it will continue in the future. Business actors are able and know the tools available on Imooji. and the perpetrators can post feeds on TS Aluminum's Instagram and edit them themselves using the templates that have been used.